Penerapan Metode Pembiasaan Membaca dalam Meningkatkan Kemampuan Menghafal Juz Amma Siswa di MI Nurul Islam Kraton Yosowilangun Lumajang - Mukhtar Zaini Dahlan (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
Al-Quran is a holy book that was revealed by Allah to the Ummi Prophet Muhammad SAW, as one of the incomparable graces for the universe. Muslims feel that it is a great worship to memorize Al-Quran ul Karim. People who memorize are highly exalted and respected. Madrasah Ibtidaiyyah Nurul Islam Kraton is an educational institution under the auspices of the Ministry of Religion which requires its students to memorize the Qur'an, especially juz amma. To obtain the data needed in this study, data collection methods were used to achieve the specified goals, while the methods used in data collection were observation, interviews and documentaries. The data collection method is carried out in a predetermined sample. In this study, researchers used qualitative data analysis of descriptive data. From the data obtained and analyzed, it can be concluded that the application of the method of reading habituation in improving students' ability to memorize juz amma at Madrasah Ibtidaiyyah Nurul Islam Kraton, Yosowilangun District, Lumajang Regency has been carried out in a good and professional manner, but needs to be improved. Among them: a) The planning application of the reading habituation method has been going well, namely leading to needs which include activities, namely, identification of needs, and identification of competencies. Which has all gone well. b) The application of the implementation of the reading habituation method has been going well, this is proven by the use of methods, media and implementation times that are as expected. c) The application for evaluating the reading habituation method is carried out in two ways, namely by test and non-test and everything is going well.